RANCANGAN AWAL DAN STRATEGI PENGEMBANGAN RUDAL JELAJAH LAPAN - Triharjanto R.H.; Sofyan E.; Riyadi A.; Mariani L.; Putro I. E. (Indonesian Journal of Aerospace, 2007)
The paper describes academic exercise of designing a cruise missile for Indonesian Armed Forces. The missile is inteded to deliver 300 kg ordinance to the distance of 1000km. The baseline design yield a vehicle with diameter of 530 mm, total length (with booster) of 4,6 m, and weight of 1300 kg. The vehicle has solid rocket booster and turbojet sustainer engine. The vehicle will have the capacity to fly to the pre-programmed target area autonomously by the use of its GNSS-INS system and horning to their target by the use of its optical target seeker or horning radar. The paper also discusses the strategy to develop the aforementioned missile. The design and the development strategy consider the limitation that Indonesian resources have in method involves capacity survey. The study resulted into missile development steps that grow in size and complexity. The milestones of the development are establishment of test vehicle with diameter of 100 mm for vehicle dynamic survey, test vehicle with diameter of 150 mm to study the deployable wing, handling of turbojet system and autopilot qualification, and test vehicle with diameter of 320 mm for seeker and dummy warhead. Keywords: Prelimenery design, guided missile.